Tumor necrosis factor-related apoptosis-inducing ligand retains its apoptosis-inducing capacity on Bcl-2- or Bcl-xL-overexpressing chemotherapy-resistant tumor cells - Walczak, Henning; Krammer, Peter H. (Cancer research, 2000)
Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) is a member of the tumor necrosis factor family and has recently been shown to exert tumoricidal activity in vivo in the absence of any observable toxicity. The signaling pathways triggered by TRAIL stimulation and the mechanisms involved in resistance against TRAIL-mediated apoptosis are still poorly defined. We show here that TRAIL-induced apoptosis involves late dissipation of mitochondrial membrane potential (ΔΨm) and cytochrome c release. These events follow activation of caspase-8 and caspase-3 and induction of DNA fragmentation. In addition, caspase-8-deficient cells are resistant against TRAIL-induced apoptosis, and inhibition of caspase-8 but not caspase-9 prevents mitochondrial permeability transition and apoptosis. In contrast, various Bcl-2- or Bcl-xL-overexpressing tumor cell lines are sensitive to TRAIL-induced apoptosis; however, they show a delay in TRAIL-induced mitochondrial permeability transition compared with control transfectants. This indicates that TRAIL-induced apoptosis depends on caspase-8 activation rather than on the disruption of mitochondrial integrity. Because most chemotherapeutic drugs used in the treatment of malignancies lead to apoptosis primarily by engagement of the mitochondrial proapoptotic machinery, we tested whether drug-resistant tumor cells retain sensitivity for TRAIL-induced apoptosis. Tumor cells overexpressing Bcl-2 or Bcl-xL become resistant to apoptosis induced by the chemotherapeutic drug etoposide. However, these cells are not protected or are only marginally protected against TRAIL-induced apoptosis. Thus, TRAIL may still kill tumors that have acquired resistance to chemotherapeutic drugs by overexpression of Bcl-2 or Bcl-xL. These data will influence future treatment strategies involving TRAIL.